2021
DOI: 10.1111/1365-2664.13871
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between local‐ and landscape‐level pesticides reduces wild bee floral visitation in pollinator‐dependent crops

Abstract: Pesticides threaten ecosystem services by reducing the abundance and diversity of beneficial arthropods, including pollinators, in agroecosystems (Carvalho, 2017). Pesticide use can result in hazards to honeybees Apis mellifera L. and wild bee species, and is considered a factor contributing to pollinator decline (Zioga et al., 2020). These non-target effects reduce crop visitation, disrupt pollination and can reduce yields (Stanley et al., 2015). However, the impacts of pesticides on pollinators are rarely st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…The specific concentrations reported for imidacloprid in croptreated pollen were high (median in watermelon: 75.4 ng g −1 ) but within the range detected in other studies of neonicotinoids in cucurbits [45][46][47]. For example, Bloom et al [45] reported the median thiamethoxam concentration in seed-treated cucumber pollen from commercial fields at 73.7 ng g −1 . Similarly, Dively & Kamel [46] found the mean imidacloprid residues in pumpkin pollen at 60.9 ng g −1 , using the same soil drench technique and product used here.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The specific concentrations reported for imidacloprid in croptreated pollen were high (median in watermelon: 75.4 ng g −1 ) but within the range detected in other studies of neonicotinoids in cucurbits [45][46][47]. For example, Bloom et al [45] reported the median thiamethoxam concentration in seed-treated cucumber pollen from commercial fields at 73.7 ng g −1 . Similarly, Dively & Kamel [46] found the mean imidacloprid residues in pumpkin pollen at 60.9 ng g −1 , using the same soil drench technique and product used here.…”
Section: Discussionsupporting
confidence: 75%
“…For example, Bloom et al . [ 45 ] reported the median thiamethoxam concentration in seed-treated cucumber pollen from commercial fields at 73.7 ng g −1 . Similarly, Dively & Kamel [ 46 ] found the mean imidacloprid residues in pumpkin pollen at 60.9 ng g −1 , using the same soil drench technique and product used here.…”
Section: Discussionmentioning
confidence: 99%
“…However, this differential response among pollinators is likely driven in part by other factors inherent to honey bee biology and management (e.g., hives are stocked at high densities, with >20,000 individuals per colony; large individual body size, and thus pesticide tolerance, compared to many solitary wild species). A recent field experiment on commercial cucurbit farms in the midwestern United States similarly found that insecticide use reduces wild bee visitation with no corresponding effect on honey bees ( 78 ). This effect is notable, since wild bees in our experiment were both most sensitive to insecticide use and most strongly correlated with crop yield.…”
Section: Discussionmentioning
confidence: 99%
“…The information-theoretic approach based on the corrected Akaike's information criterion (AICc) was applied to remove non-signi cant terms (Grueber et al, 2011). We used the "dredge" and "get.models" functions in the R package MuMIn (Bartoń, 2019) to generate all possible models and selected the top ranked models with a ΔAICc value (i.e., AICc -AICc min ) < 2 (Bloom et al, 2021). The variance expansion factor (VIF) of models was calculated to evaluate the collinearity between explanatory variables.…”
Section: Discussionmentioning
confidence: 99%